Analisis Pengaruh Belanja Total Tenaga Kerja Ekspor Terhadap Pdrb Di Kabupaten Klaten Tahun 1996 2015 - Saputro, Lilik Joko; , Drs.Yuni Prihadi Utomo,.M.M (2017)
Singer study entitled "Analysis of Effect of Expenditure Amount, Labor, Export Against the GDP In Klaten Regency Year 1996-2015". Singer study aims to review counting direction, and the influence of Expenditure Amount, Labor, Export Against the GDP In Klaten district. Operating Data Used hearts singer research is secondary data Data Form of total expenditure, labor, exports and the GDP In Klaten district. The analytical method used is ordinary least squares (OLS) that is to review counting direction, and the influence of free variable (PT) Against Unrestricted variable(dependent). Can singer research concluded that the total expenditure variable has a positive effect against the GDP with regression coefficient value 5,69E-06. Also the same things are at variable workforce The positive effect against the GDP with regression coefficient of 5.528709. As for the reviews on export variables have a negative effect against the GDP with regression coefficient of 0.024117. Classical assumption that test results from testing multikolinierity no problem, normality test data showing the rest of normally distributed, the linearity test showed yang used linear models, testing heteroskedasticity no problem, and tocorrelation test no problem.